Evaluation of efficiency the commercial influenza vaccines used in Iraq by ELISA technique. - Nafea S .Jasim; Shiema Abid- Jabber (Al-Qadisiyah Journal of Pure Science, 2018)
This study was done to evaluate types of  inactivated  influenza vaccines in poultry field in  Iraq to reduce high incidence  outbreaks  of  disease to minimize high ecomoical losses in  broiler and  layers . the efficacy of vaccines  on immune response was evaluated depending  on indirect immune sorbent assay (ELISA) test at  (18,25,32,40) days of  age in experiment  consisting  of 800 chicks .The results revealed high significant titer of  immune response  in the vaccinated  groups  comparison with  control group , and results showed significant  titer of  immunity  response in  subgroups , 2, 4 comparison  with  other  subgroups . the  influenza vaccine  from intervet  company  showed immune response more than other vaccines.